Kearifan Lingkungan yang Diungkapkan dalam Uluan Pantun dari Perspektif Interaksionisme Simbolik - Yenrizal Yenrizal; Muhammad Sirozi; Ahmad Muhaimin (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
Traditional oral literature has long served to preserve and pass down cultural values and wisdom. In the Uluan society of South Sumatra, pantun, a traditional Malay poetic form, plays a central role in communicating messages related to societal norms and environmental stewardship. This study explores the environmental wisdom embedded in Uluan pantun, using a symbolic interactionism perspective to examine how these oral traditions convey ecological messages. The research employs a qualitative methodology with an ethnographic communication approach. Data were collected through documentation of ancient pantun texts, in-depth interviews with cultural practitioners and local community members, participatory observation in key Uluan regions, and focus group discussions (FGD) to provide a comprehensive view of how pantun is actualized in contemporary environmental conservation efforts. The results show that pantun is an important medium for conveying explicit and implicit messages about the natural environment, reflecting the community’s deep connection with nature. However, modern challenges such as deforestation and land degradation have threatened the sustainability of these traditions. The novelty of this research lies in its examination of pantun as an instrument for ecological communication, an area that has received little attention in previous studies. The findings imply that revitalizing the ecological messages within pantun could significantly promote environmental awareness and community-driven conservation in Uluan society today.